Deep vein thrombosis in patient with pulmonary tuberculosis: a rare and interesting causative link? - Saini, Rohin; Mishra, Arvind; Gupta, Kamlesh Kumar; Kallani, Monika (International Journal of Advances in Medicine, 2019)
Pulmonary tuberculosis is a devastating disease affecting millions of people in developing countries such as India. Many complications of this disease are known, however only few of its hematological complications have been reported. Discovery of its unknown thrombogenic potential is one such disturbing new entity. Tuberculosis can induce a hypercoagulable state and can lead to thromboembolic complications and deep vein thrombosis. Here we report an interesting and rare case of 20-year-old male, newly diagnosed case of Pulmonary Tuberculosis presenting with complaints of acute onset right lower limb swelling and pain. He was diagnosed with thrombosis of external iliac vein. All possible causes for a provoked deep vein thrombosis were evaluated for and ruled out. The patient was started with first line anti tubercular treatment-rifampicin, isoniazid, pyrizinamide, ethambutol along with anti-thrombotics injection enoxaparin and warfarin and followed up for 6 months. He made complete recovery of both his pulmonary and limb disease.